2016
DOI: 10.1128/aac.01543-15
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Doripenem in Critically Ill Patients with Sepsis in a Malaysian Intensive Care Unit

Abstract: g Doripenem has been recently introduced in Malaysia and is used for severe infections in the intensive care unit. However, limited data currently exist to guide optimal dosing in this scenario. We aimed to describe the population pharmacokinetics of doripenem in Malaysian critically ill patients with sepsis and use Monte Carlo dosing simulations to develop clinically relevant dosing guidelines for these patients. In this pharmacokinetic study, 12 critically ill adult patients with sepsis receiving 500 mg of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Abdul-Aziz et al performed population pharmacokinetics analysis of DRPM using a nonlinear mixed-effects modeling in 12 critically ill patients with sepsis in a Malaysian ICU. 28) They showed the typical total clearance and distribution volume of DRPM were 0.14 L/kg/h and 0.47 L/kg, respectively, which are almost the same parameters (Total clearance: 0.14 L/kg/h, distribution volume: 0.40 L/kg) as the patients of our report. However, previous Monte Carlo simulation revealed that the PK/PD breakpoints for standard or higher DRPM regimen in every group with Ccr of 70, 50 and 30 mL/min were 2 or 4 µg/mL, respectively, 28) which is slightly higher than that in present study.…”
Section: Discussionsupporting
confidence: 60%
“…Abdul-Aziz et al performed population pharmacokinetics analysis of DRPM using a nonlinear mixed-effects modeling in 12 critically ill patients with sepsis in a Malaysian ICU. 28) They showed the typical total clearance and distribution volume of DRPM were 0.14 L/kg/h and 0.47 L/kg, respectively, which are almost the same parameters (Total clearance: 0.14 L/kg/h, distribution volume: 0.40 L/kg) as the patients of our report. However, previous Monte Carlo simulation revealed that the PK/PD breakpoints for standard or higher DRPM regimen in every group with Ccr of 70, 50 and 30 mL/min were 2 or 4 µg/mL, respectively, 28) which is slightly higher than that in present study.…”
Section: Discussionsupporting
confidence: 60%
“…The lower doripenem CL in Korean patients with either normal or lower levels of renal function, possibly due to differences in BW and body mass between Korean and other populations (42,43), may result in a greater chance of attaining a PK or PD target, even with lower doripenem doses. Nevertheless, a cautious interpretation of our results is necessary until a firmer understanding of the interethnic differences in the pharmacokinetics of doripenem is obtained, because several recent studies did not show significant differences in doripenem PK among different popu-lations (15,16). Data regarding ethnic differences in PK/PD would be precious for the optimization and individualization of doripenem dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are conflicting results regarding the association between low or undetectable blood ␤-lactam levels and poor clinical outcomes in infected patients (27,28), the increased glomerular filtration and drug elimination caused by augmented renal function is known to predict subtherapeutic ␤-lactam concentrations (20,29). Limited data evaluating doripenem PK in patients with augmented renal function indicate a decreased PTA in such patients, which favors the use of extended infusions (16,21). Furthermore, one recent study comparing the clinical outcomes of patients with ventilator-associated pneumonia due to Gram-negative bacteria treated with doripenem versus imipenem-cilastatin suggested that doripenem-treated patients with a supranormal renal function (CL CR Ն 150 ml/min) had poor clinical cure rates (44%, 8/18 patients) (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in antibiotic Vd have been noted in critically ill patients [6,[53][54][55][56][57], and the contributing factors are discussed below.…”
Section: Changes Of Volume Of Distributionmentioning
confidence: 99%